Application of Hough transform in contact wire wear detection algorithm - NIE Xiao; WANG Feng; WANG Tao; CHEN Xieqi (机车电传动)
When the locomotive is running on an electrified railway, it is necessary to ensure the continuous and reliable power supply of the catenary system. The contact wire wear will affect the current-receiving quality, and it needs to be monitored in real time. For the low accuracy and poor robustness of the current contact wire wear detection system, a contact wire wear detection algorithm based on Hough transform was presented. Firstly, the profile data collected by the structured light device was preprocessed with mean shift algorithm and cubic spline interpolation; secondly, the center of the contact wire was determined according to Hough transform; finally, the wear based on the geometric characteristics of contact wire was calculated . Experimental results show that the method has better accuracy and robustness compared with the classical least squares fitting, and can meet the real-time detection requirements.